Boosting Self‐Assembly Diversity in the Solid‐State by Chiral/Non‐Chiral ZnII‐Porphyrin Crystallization. Issue 49 (30th July 2018) - Qian, Wenjie; González‐Campo, Arántzazu; Pérez‐Rodríguez, Ana; Rodríguez‐Hermida, Sabina; Imaz, Inhaz; Wurst, Klaus; Maspoch, Daniel; Ruiz, Eliseo; Ocal, Carmen; Barrena, Esther; Amabilino, David B.; Aliaga‐Alcalde, Núria
Abstract: A chiral Zn II porphyrin derivative1 and its achiral analogue2 were studied in the solid state. Considering the rich molecular recognition of designed metalloporphyrins1 and2 and their tendency to crystallize, they were recrystallized from two solvent mixtures (CH2 Cl2 /CH3 OH and CH2 Cl2 /hexane). As a result, four different crystalline arrangements (1 a, b and2 a, b, from 0D to 2D) were obtained. Solid‐state studies were performed on all the species to analyze the role played by chirality, solvent mixtures, and surfaces (mica and HOPG) in the supramolecular arrangements. By means of combinations of solvents and substrates a variety of microsized species was obtained, from vesicles to flower‐shaped arrays, including geometrical microcrystals. Overall, the results emphasize the environmental susceptibility of metalloporphyrins and how this feature must be taken into account in their design. Abstract : Metalloporphyrin aggregation : New perspectives on metalloporphyrin aggregates were obtained by means of chiral and achiral Zn porphyrin analogues, which were crystallized by slow liquid–liquid diffusion with two sets of solvents (CH2 Cl2 /MeOH and CH2 Cl2 /hexanes) to give different crystalline architectures for each combination (see figure). Solid‐state analysis of these aggregates revealed the roles played by chirality, solvent mixtures and surfaces in the supramolecular arrangements.